(untitled) (Journal of Comparative Social Work, 2014)
As definitions of “family” have evolved in the US over the past several decades, so too has child welfare agencies’ need to provide appropriate and meaningful services. This article discusses the findings and conclusions drawn from a case study involving two different types of social work agencies: Native American child welfare and not- for-profit family services. Within this discussion, the authors use their findings from case study vignette focus groups to explore how the definitions of family impact the provision of services.At each agency, participants addressed issues surrounding domestic violence, teen pregnancy, child welfare involvement and the inclusion of extended families as part of client’s support network. By focusing on the changing social concept of “family,” the study’s respondents discussed the need for direct practice using broader, more inclusive approaches to family and child welfare. Through the comparison of two agencies which serve different demographics, the article makes clear that further study is needed, and a wider scope must be considered, in order to adequately serve America’s expanding population in need of family services, direct practice and extended support.